Reconfiguring Educational Epistemology in the Age of Artificial Intelligence: Between Knowledge Authority and Learning Automation - Risza Presty Rumani (Journal of Pedagogi, 2026)
This study examines the epistemological transformation of education in the era of artificial intelligence (AI), focusing on the shifting authority of knowledge, the automation of learning processes, and their implications for educational practices. As AI increasingly mediates how knowledge is produced, validated, and accessed, traditional human-centered epistemic structures are being redefined. This research employs a qualitative approach using a Systematic Literature Review (SLR), analyzing recent peer-reviewed journal articles from databases such as Scopus, Web of Science, and Google Scholar. Data were collected through a rigorous screening process based on relevance and methodological quality, and analyzed using thematic and content analysis to identify key patterns across epistemological, technological, and ethical dimensions. The findings reveal that knowledge authority is becoming distributed between humans and algorithmic systems, while AI-driven automation enhances efficiency and personalization but risks reducing critical engagement and conceptual depth. Additionally, the emergence of data-driven and opaque knowledge systems requires new competencies, including AI literacy and epistemic awareness. The study concludes that a comprehensive reconfiguration of educational epistemology is necessary, emphasizing the integration of technological innovation with critical thinking, ethical responsibility, and epistemic justice to ensure meaningful and sustainable learning in the AI era